PENGUKURAN KONSENTRASI TIMBAL (Pb) DALAM DEBU DI RUMAH PENDUDUK KAWASAN DESA KADU, KECAMATAN CURUG, TANGERANG â BANTEN - Bobu, Fetronela R.; Noor, Johan A.E.; bunawas, Bunawas (Physics Student Journal, 2013)
The processing industry of ex accu can give bad impact to the air quality. Dust fromÂ  industrial activity is one ofÂ  main lead exposure (Pb). The aim of this researh is to knowÂ  Pb concentration in dust. This research have been done on the resident area at DesaKadu, Tangerang, Banten. TheÂ  sample took at three region.Â  This region is in recycle ex accu industrial area (RT 3a, RT 3b and RT 4a) by total respondents, 51. This research is observational quantitative with cross sectional design. It was look Pb concentration in floorâs dust and sandâs dust in the same period.Â  The Pb concentration measurement were conducted by X ray Fluorescence (XRF) and to measure supporting variable were conducted by kuisioner. The results show that Pbconcentration in floorâs dust 442-558 Î¼g/ft2 and in sandâs dust 505-5066 Î¼g/ft2. The results show that Pb concentration had out of standard. Â  Keywords : recycle ex accu industry, dust, lead (Pb), X-ray Fluorescene (XRF)